Hubungan Jenis Kelamin dengan Gangguan Kognitif Pasca Stroke Iskemik Serangan Pertama dengan Lesi Hemisfer Kiri - Prasetyo, Bagus Dwi; Suroto, .; Mirawati, Diah Kurnia (Nexus Kedokteran Klinik, 2013)
Background: Stroke is a cerebrovascular disease which until now the third leading cause of death in the world. Stroke can cause physical disability to psychosocial disfunction, such as cognitive impairment. This study aimed to analyze the relationship between gender and cognitive impairment after ischemic stroke first attack with left hemisphere lesions. Methods: This type of research is an observational analytic with cross-sectional approach. Sample of this study were post ischemic stroke Â patients with a total sample of 60 people. Measuring instrument used was Mini Mental State Examination (MMSE), and performed data analysis with multiple logistic regression analysis. Results: After the study on a sample of 60 post-stroke patients with a first ischemic attack left hemisphere lesions found post-stroke cognitive impairment in male patients amounted to 46.7%, whereas in female patients by 30%. The results of calculations using Binary Logistic Regression Analysis obtained OR = 0.14; CI 95% 0025 to 0794 and p = 0026. From these data showed statistically significant relationship between the gender with cognitive impairment after ischemic stroke first attack with left hemisphere lesions. Conclusions: There is a statistically significant relationship between gender to cognitive impairment on post-ischemic stroke patients. This conclusion is drawn after controlling for the effects of confounding factors such as age, level of education and cardiovascular risk factors: diabetes mellitus, hypertension, dyslipidemia. Keywords: gender, cognitive impairment, ischemic stroke